Differentiated thyroid cancer in patients with resistance to thyroid hormone syndrome. A novel case and a review of the literature - Vinagre, João; Borges, Fátima; Costa, António; Alvelos, Maria Inês; Mazeto, Glaúcia; Sobrinho-Simões, Manuel; Soares, Paula (Frontiers in Molecular Biosciences, 2014)
Resistance to thyroid hormone (RTH) represents a syndrome in which patients present elevated circulating thyroid hormones in the presence of non-suppressed TSH. We report a novel case where a patient with RTH presented a differentiated thyroid cancer. A19 year-old female had been referred due to thyroid disease that disclosed features characteristic of a RTH. During the follow up it was detected a follicular tumour that led to the recommendation for thyroid surgical ablation, where an incidental papillary thyroid microcarcinoma (mPTC) was found. The increase of thyroglobulin (TG) levels following thyroid removal referred the patient for radioiodine treatment. Post-treatment, it was detected jugular adenopathies and the patient was subjected to cervical lymph node drainage where metastases of the mPTC were found. RTH syndrome was confirmed by the detection of a THRB germline mutation. A BRAF mutation was also found in the mPTC but not detected in the follicular adenoma or normal adjacent tissue. The young age of the patient, the rarity of BRAF mutations in childhood and the high dissemination of the malignancy, lead us to the speculation that increased TSH stimulation in a RTH background and oncogenic activation of BRAF could have served as (co) drivers and might have triggered an advanced stage of the neoplastic disease. These findings together with a review of published cases add novel information to the management of RTH patients with differentiated thyroid cancer.